Experimentation in securities market structure and regulation in China: from state to market. Issue 2 (2nd July 2016) - Li, Xiao; MacNeil, Iain
ABSTRACT: A key feature of the socialist market economy in China is the development of securities markets so as to facilitate entrepreneurship. With the national securities market now well established attention has shifted to the development of lower-tier markets that may be able to meet the financing needs of smaller-scale enterprises. In this article we examine how the concept of experimentation has been applied to the process of developing such markets and the regulatory framework in which they operate. We begin with a survey and critique of the policy and regulatory framework within which lower-tier markets have evolved. We argue that experimentation has been important in China but that it operates in a unique way as a result of the institutional structure in which securities markets are located. We then focus more specifically on the regulatory framework for lower-tier markets and present two case studies focused on the establishment and operation of two local equity exchanges in a single province (LiaoNing). While this evidence supports our view on the significance of experimentation it also highlights the problems associated with developing lower-tier securities markets within the current policy framework.